Stability of Striga gesnerioides resistance mechanism in cowpea under high- infestation level, low soil fertility and drought stresses - Muranaka S; Fatokun, C.A.; Boukar, O. (2011)
Parasitic weed, Striga gesnerioides is a major constraint to cowpea [Vigna unguiculata (L.) Walp.] productivity in West and Central Africa. Efforts are being made to identify major genes that determine the race specific resistances to S. gesnerioides in cowpea and to develop resistant varieties with suitable agricultural traits. However, detailed mechanisms that induce the resistances are unclear and the effects of environmental stresses under the field conditions on the resistance to S. gesnerioides have not been reported. To evaluate the stability of resistance mechanisms to S. gesnerioides race SG3 in cowpea, the effects of high infestation rate and combined environmental stresses on the resistance to S. gesnerioides were investigated. Under high (60,000 germinable seed per pot) infestation rate, no S. gesnerioides attachments were observed on the roots of three resistant genotypes B301, IT97K-499-35 and IT98K-205-8, while susceptible Dan Ila and IT98D-1399 showed a number of attachments even at the lowest infestation rate. Low soil fertility and drought stress could reduce the growth of cowpea. However, these stresses did not alter the resistance of IT97K-499-35 and IT98K-205-8 to S. gesnerioides. Greater growth inhibition was observed in IT98D-1399 under the combination of S. gesnerioides infestation and drought stress compared to Dan Ila which also showed a number of attachments. This suggests that the restricted root development due to S. gesnerioides infection observed in IT98D-1399 may restrict water uptake from the soil, and consequently magnified the effect of drought stress on the host s productivity. The results obtained indicate that the physiological mechanisms attributable to the resistance to S. gesnerioides race SG3 in cowpea could perform stably under high seed infestation condition, and combined low soil fertility and drought stresses.